Clinicopathological analysis of biphenotypic sinonasal sarcoma： a case report - GONG Jingqing, CAO Duanrong, ZHUANG Yixin, QIU Li, LI Xiaoming (Zhenduanxue lilun yu shijian, 2025)
This study reported a rare case of biphenotypic sinonasal sarcoma (BSNS) and analyzed its clinicopathological features. The patient was a 35-year-old male admitted due to "recurrent right-sided nasal discharge mixed with blood for over three months". Endoscopic resection of a mass in the right nasal cavity, paranasal sinuses, and skull base was performed, followed by postoperative pathological biopsy. Under light microscopy, the tumor had an ill-defined boundary, with a surface covered by ciliated columnar epithelium. Focal squamous metaplasia of the ciliated epithelial cells was observed, along with mucosal invagination, dilation, and gland hyperplasia. The tumor was composed of diffusely distributed spindle cells densely arranged in bundles, woven, or herringbone patterns, without obvious cellular atypia. The chromatin was fine, and no obvious mitotic figures or necrosis were observed. In the stroma, thin-walled, dilated, and branched blood vessels resembling antlers were observed, and no definite regions of rhabdomyoblastic differentiation were identified. Immunophenotyping of the tumor tissue showed positive expression of Vimentin, H-Caldesmon, INI-1, Bcl-2, and CD99. Partial positive expression of Calponin, S100, MyoD1, and SMA. The Ki-67 index was approximately 35% in hotspot regions. Myogenin, STAT6, SOX-10, Desmin, β-catenin, CK, CD34, NSE, PR, and EMA were negative. Genetic testing showed PAX3 gene rearrangement, with positive FISH results. No rearrangement of the SYT gene was found, and the FISH result was negative. The clinical features of this case were nonspecific, but histologically, relatively typical features of BSNS were present, including gland-like structures formed by ciliated columnar epithelium invaginating into the spindle cell component with cystic dilation, or proliferative respiratory glands present within the spindle cell component. Differentiation of BSNS from other spindle cell tumors should be based on a comprehensive assessment of the site of origin in the nasal cavity and paranasal sinuses, the composition of relatively bland spindle cells, relatively typical histological features, expression of myogenic and neurogenic immunomarkers, and the characteristic PAX3 gene rearrangement.